Strategi Guru PAI dalam Mengimplementasikan Kurikulum Merdeka di MTs Arrabbi Tamansuruh Tahun Ajaran 2024/2025 - Risa Pratiwi; Wisnu Utomo; Mar Syahid (CV. Lentera Literasi Indonesia, 2026)
This research aims to describe the strategies used by Islamic Religious Education (PAI) teachers in implementing the Merdeka Curriculum at MTs Arrabbi Tamansuruh in the 2024/2025 academic year and to identify the supporting and inhibiting factors in the implementation process. The research employed a qualitative approach with a descriptive method. Data collection techniques included interviews, observation, and documentation. The informants in this study consisted of the head of the madrasah, PAI teachers, and students. The results of the study show that PAI teachers applied various active and contextual learning strategies such as group discussions, project-based learning, and collaborative approaches that are student-centered. These strategies aim to increase student participation and relate Islamic subject matter to real-life situations. However, teachers also faced several challenges, including difficulties in formulating appropriate learning outcome indicators and the lack of active participation from some students. Supporting factors in the implementation of the Merdeka Curriculum include the curriculum's flexibility and the teachers’ enthusiasm for innovation. Meanwhile, inhibiting factors involve limited technical guidelines and students’ readiness for independent learning. This study illustrates that the success of implementing the Merdeka Curriculum largely depends on the appropriate and adaptive strategies employed by PAI teachers in addressing the dynamics of the learning process.